Validation of a rapid type 1 diabetes autoantibody screening assay for community‐based screening of organ donors to identify subjects at increased risk for the disease. (4th May 2016) - Wasserfall, C.; Montgomery, E.; Yu, L.; Michels, A.; Gianani, R.; Pugliese, A.; Nierras, C.; Kaddis, J. S.; Schatz, D. A.; Bonifacio, E.; Atkinson, M. A.
Summary: The Network for Pancreatic Organ donors with Diabetes (nPOD) programme was developed in response to an unmet research need for human pancreatic tissue obtained from individuals with type 1 diabetes mellitus and people at increased risk [i.e. autoantibody (AAb)‐positive] for the disease. This necessitated the establishment of a type 1 diabetes‐specific AAb screening platform for organ procurement organizations (OPOs). Assay protocols for commercially available enzyme‐linked immunosorbent assays (elisa s) determining AAb against glutamic acid decarboxylase (GADA), insulinoma‐associated protein‐2 (IA‐2A) and zinc transporter‐8 (ZnT8A) were modified to identify AAb‐positive donors within strict time requirements associated with organ donation programmes. These rapidelisa s were evaluated by the international islet AAb standardization programme (IASP) and used by OPO laboratories as an adjunct to routine serological tests evaluating donors for organ transplantation. The rapidelisa s performed well in three IASPs (2011, 2013, 2015) with 98‐100% specificity for all three assays, including sensitivities of 64–82% (GADA), 60–64% (IA‐2A) and 62–68% (ZnT8A). Since 2009, nPOD has screened 4442 organ donors by rapidelisa ; 250 (5·6%) were identified as positive for one AAb and 14 (0.3%) for multiple AAb with 20 of these cases received by nPOD for follow‐up studies (14 GADA+, two IA‐2A +, four multiple AAb‐positive). Rapid screening for type 1 diabetes‐associated AAb in organ donors is feasible, allowing for identification of non‐diabetic, high‐risk individuals and procurement of valuable tissues for natural history studies of this disease.